Abordaje nutricional en pacientes hospitalizados con Covid-19 - Martínez Iturriaga, Sheila (Nutrición Clínica y Dietética Hospitalaria, 2020)
Introduction: Nutritional support is a central pillar of comprehensive treatment. The recommendations suggest starting with protein supplements and enteral nutrition specific for respiratory distress. Objectives: To characterize patients with nutritional risk admitted by COVID-19, describe nutritional procedures, and assess the impact of admission on nutritional status. Material and methods: Observational, descriptive and retrospective study of admissions by COVID-19 from March 15 to April 25, 2020 Inclusion criteria: income > 3 days and PCR, protein and albumin values at admission and discharge. Computer tools: FarHo® and HCI® del. Statistics: SPSS®. Results: 45 patients in the study, 55% men with an average age of 65 years. The average values of protein and albumin at entry and discharge were in range, with a slight decrease for the high values, especially of albumin. (p>0.05). The average number of days of admission is 7.32 days. 40% were patients with nutritional risk. Nutritional intervention was carried out on 46% of the patients and 50%managed to increase the protein figures at discharge. The differences are not statistically significant. (p>0.05). There are no significant differences between the values in the entry and discharge over time (p>0.05). Discussion: We should consider protocolizing a correct approach to hospital malnutrition in our center and systematize nutritional care in this vulnerable population. Conclusions: 1. Forty% of the patients admitted for COVID-19 presented nutritional risk. 2. The nutritional interventions carried out consisted of providing hypercaloric and hyperprotein supplements and specific enteral diets for respiratory failure. The differences in protein and albumin, at admission and discharge are not significant. 3. Time in hospital for COVID has no effect on the nutritional status of patients.